Bahasa Jepang Pelaku Pariwisata di Pantai Kuta - Budiana, I Made (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2019)
Abstract      The arrival of tourists from Japan not only requires tour guides, but also requires human resources who have adequate language competency standards to work professionally. In this study discussed about the variety of Japanese travel agents in the Kuta beach area. This topic was raised because researchers directly saw a lot of tourism actors on Kuta beach, such as hawkers, hair braid services, sellers of nail polish, temporary tattoo, massage services, surfing guide services that use Japanese. However, the Japanese language used is still far from the standard language in Japanese. The variety of Japanese used by tourism actors is very diverse, but irregular so it seems impolite. The purpose of this study is to get a clear picture of Japanese language competence of tourism actors in Kuta beach area. And the results of this study can be used as a basis for making scientific documentation or simple dictionaries that can help tour guides, especially Japanese tour guides.   Keywords: guide, tourism, Japanese